High triplet energy materials for efficient exciplex-based and full-TADF-based white OLEDs. (June 2020) - Tan, Xiaofeng; Volyniuk, Dmytro; Matulaitis, Tomas; Keruckas, Jonas; Ivaniuk, Khrystyna; Helzhynskyy, Igor; Stakhira, Pavlo; Grazulevicius, Juozas Vidas
Abstract: Materials with high triplet energies have attracted great attention for their application in exciplex-based or thermally activated delayed fluorescence-based organic light-emitting diodes. To study the correlation between triplet energy and chemical structure, six compounds with typical donor-acceptor-donor structures were designed, synthesized, and characterized. Through the adjustment of molecular configuration by weakening the strengths of donors and increasing the angles between donors and acceptors, the triplet energies of the materials were gradually increased from 2.5 to 3.0 eV. Three exciplex-based organic light-emitting diodes containing one of the synthesized compounds were fabricated, which exhibited efficient blue, green-yellow, and white thermally activated delayed fluorescence. Blue and green-yellow organic light-emitting diodes exhibited the maximum external quantum efficiencies of 9.1% and 8.3%, respectively. White organic light-emitting diodes showed turn-on voltage of 4.8 V, high maximum luminance of 18474 cdm -2, and maximum external quantum efficiency of 10.6%. Maximum external quantum efficiencies of blue and white organic light-emitting diodes were close to the record values observed for all-exciplex-based blue and white organic light-emitting diodes. Highlights: Noval structures of Emitting materials: A series of donor-acceptor-donor compounds based on novel electron-donor units with central oxa-hexatomic rings. New strategy for enhancing the triplet energies: Through the adjustment of molecular configuration by weakening the strengths of donors and increasing the angles between donors and acceptors, the triplet energies of the materials were gradually increased from 2.5 to 3.0 eV. Good device performance close to world record: The EQE of exciplex-based and TADF-based OLEDs are close to the world record. Blue and white exciplex-based OLEDs based on this material exhibited EQE of 9.1% and 10.6%, respectively.